THE CORRELATION BETWEEN KNOWLEDGE LEVEL OF COVID-19 VACCINATION AND READINESS TO VACCINATE COVID-19 DOSE 3 (BOOSTER) IN SOUTH RENGASDENGKLOK VILLAGE IN 2022 - Aprilia, Fina; Lisna Agustina; Baltasar Serilus Sanggu Dedu (Rena Cipta Mandiri, 2022)
Coronavirus Disease 2019 or known as COVID-19 is a virus that was discovered in the city of Wuhan, China in December 2019. This virus is categorized as an infectious disease that causes respiratory infections caused by Severe Acute Respiratory Syndrome Coronavirus 2 or commonly referred to as SARS-CoV-2. 2. Early protection during a pandemic is needed so that the pandemic is immediately resolved and ended. Vaccines are the main key in reducing the transmission rate of COVID-19. The implementation of this COVID-19 vaccination requires knowledge, as well as the public's willingness to carry out the COVID-19 vaccination. Knowing the relationship of Relationship between Knowledge Level of COVID-19 Vaccination and Readiness to Vaccinate COVID-19 Dose 3 (Booster) in South Rengasdengklok Village in 2022. This research method is quantitative design using cross sectional analytical research type design. The population of this study is the community of South Rengasdengklok Village RT 002 RT 006 RW 001,using purposive sampling techniques. Based on the results of statistical analysis using the chi square test obtained a p value of 0,000 ≤ 0.05. This indicates that H0 was rejected. There is a Relationship between Knowledge Level of COVID-19 Vaccination and Readiness to Vaccinate COVID-19 Dose 3 (Booster) in South Rengasdengklok Village in 2022.